2007
DOI: 10.1159/000108956
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Pathways and Evidence-Based Perturbations in Acute Pancreatitis

Abstract: Nitric oxide (NO) is a gaseous neurotransmitter, a vasodilator and paracrine regulator. In the pancreas, NO regulates normal pancreatic exocrine secretion, endocrine pancreatic insulin secretion and pancreatic microvascular blood flow. NO has multiple species and is produced de novo by 3 NO synthase enzymes. Endothelial NO synthase reduces the severity of the initial phase of experimental acute pancreatitis (AP). Cigarette smoking and chronic alcohol use disrupt normal NO pathways and are associated with pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…However, there is not agreement about its beneficial or detrimental role in this disease [57] ; moreover, an increase in NO has been suggested in SAP in humans [58] , but this issue is not yet clear [59] . We have demonstrated, by using an experimental model of necrotizing AP in rats, that NO and other va sodilators may exert a beneficial effect on SAP when they are administered before induction of pancreatitis [55] .…”
Section: From Local Pancreatic Damage To Systemic Effectsmentioning
confidence: 99%
“…However, there is not agreement about its beneficial or detrimental role in this disease [57] ; moreover, an increase in NO has been suggested in SAP in humans [58] , but this issue is not yet clear [59] . We have demonstrated, by using an experimental model of necrotizing AP in rats, that NO and other va sodilators may exert a beneficial effect on SAP when they are administered before induction of pancreatitis [55] .…”
Section: From Local Pancreatic Damage To Systemic Effectsmentioning
confidence: 99%
“…Nitric oxide, a gaseous neurotransmitter, vasodilator and paracrine regulator is involved in the physiological functions of the pancreas including exocrine and endocrine secretion (insulin) as well as in regulating pancreatic microvascular blood flow [75]. It thus plays an important role in physiological and may possibly be involved in the development AP [76].…”
Section: Neurotransmitters and Oxidative Stress (Including Nitric Oximentioning
confidence: 99%
“…It has been suggested that certain amount of NO production has beneficial effects in experimental edematous acute pancreatitis, but uncontrolled over-production of NO may be detrimental [176]. Endothelial NO synthase (eNOS) reduces the severity of the initial phase of experimental acute pancreatitis [177]. NO production and NOS expression seem to be differentially regulated temporally and in magnitude in the pancreas and lungs in response to caerulein hyperstimula- Fig.…”
Section: Nitrosative Stress In Acute Pancreatitismentioning
confidence: 99%